Governance and sustainability of responsible research and innovation processes : cases and experiences /: cases and experiences. (2018) - Ferri, Fernando; Dwyer, Ned; Raicevich, Saša; Grifoni, Patrizia, 1959-; Altiok, Husne; Andersen, Hans Thor; Laourēs, Giannēs; Silvestri, Cecilia
No abstract available